Family Communication Patterns in Enhancing Learning Motivation and Academic Achievement Among Students of Ciputra University Surabaya - Jason Jeremy Sutedjo; Bernard Realino Danu Kristanto (Green Publisher Indonesia, 2024)
Every parent wants good things to happen to their child, one of which is for their child to have a bright future. Therefore, it is important for parents and children to have a relationship that is built on healthy and effective communication. However, communication barriers often occur between parents and children which are influenced by several factors such as experience and age. Interpersonal communication is a form of communication that occurs directly between individuals in face-to-face conditions, this also includes interactions within the family, such as parents and children. Nowadays, in order to get the best education, children will go abroad and away from their parents. This will then reduce communication that occur between them and their parents. Many Ciputra University students come from various cities spread throughout Indonesia, not infrequently they also have brilliant achievement. In this study, researchers are interested in examining the role of family communication patterns in increasing learning motivation and achievement in Ciputra University students, especially those who are migrating and have distance barriers in communicating with parent.